The Influence Of Tiktok Video Quality And Posting Frequency On Consumers’ Purchase Intention - Rafidha Yasmin Tarigan; Elfitra Desy Surya; Dewi Nurmasari Pane (LPPJPHKI Universitas Dehasen Bengkulu, 2026)
The development of social media, particularly TikTok, has encouraged the use of short videos as an effective digital marketing strategy in influencing consumer behavior. This study aims to analyze the influence of TikTok short video quality and posting frequency on consumers’ purchase intention. The research employs a quantitative approach using a survey method involving 150 respondents who are TikTok users. Data were collected through questionnaires and analyzed using multiple linear regression. The instrument quality test results indicate that all research indicators are valid and reliable. The regression analysis reveals that TikTok short video quality has a positive and significant effect on consumers’ purchase intention, and similarly, TikTok short video posting frequency also has a positive and significant effect. Simultaneously, TikTok short video quality and posting frequency are proven to have a significant effect on consumers’ purchase intention, with a coefficient of determination of 54.9 percent. These findings indicate that the combination of high-quality content and optimal posting frequency can effectively enhance consumers’ purchase intention. This study provides practical implications for businesses and digital marketers in developing integrated TikTok marketing strategies by emphasizing content quality and proper management of posting frequency..